Cover Image. (23rd February 2021) - Lemoine, Caroline; Brandt, Katherine; Carlos Caicedo, Juan; Superina, Riccardo
Abstract : The cover image is based on the Original Article Internal split liver transplants reduce the waiting list time for teenagers with a low calculated Model for End‐stage Liver Disease score by Caroline Lemoine et al., https://doi.org/10.1111/petr.13874 .